Post hoc analysis of the Cluster Randomized Usual Care versus Caduet Investigation Assessing Long-term risk (CRUCIAL) trial. (June 2013) - Hradec, Jaromír; Zamorano, José; Sutradhar, Santosh
Abstract Objective: A proactive, multifactorial intervention strategy incorporating single-pill amlodipine/atorvastatin (SPAA) (5–10/10 mg up-titrated to 5–10/20 mg, where approved) is more effective than physician's usual care (UC) for reducing calculated 10 year coronary heart disease (CHD) risk, in patients with hypertension and additional risk factors (CRUCIAL trial: Curr Med Res Opin 2011;27:821--33). As SPAA combinations containing atorvastatin 20 mg are not approved in some countries, this post hoc analysis investigated the efficacy and safety of a proactive intervention strategy incorporating low-dose SPAA (5/10 or 10/10 mg) only (low-dose PI) versus UC. Methods: Of 1461 CRUCIAL participants (35–79 years; hypertension and ≥3 additional risk factors; no CHD; total cholesterol ≤6.5 mmol/L), 105 were prescribed SPAA containing 20 mg atorvastatin and excluded. The primary endpoint was difference between treatment arms in Framingham 10 year CHD risk after 52 weeks; secondary assessments included difference in calculated CHD risk at Week 16; SCORE cardiovascular mortality (Week 16 and 52); blood pressure (BP)/lipid parameters; adverse events (AEs). Results: Baseline BP (149.2/89.2 vs. 144.3/86.5 mmHg) and calculated CHD risk (19.6% vs. 18.1%) were higher for low-dose PI (n = 655) versus UC (n = 657) patients. Least-squares mean treatment difference (low-dose PI vs. UC) in calculated 10 year CHD risk was −26.8 (95% CI: −31.7, −22.0; p < 0.001) after 52 weeks' follow-up and −24.8 (−29.8, −19.9; p < 0.001) after 16 weeks' follow-up. Treatment difference in SCORE mortality was −20.1 (−24.7, −15.6; p < 0.001) and −22.4 (−26.8, −18.0; p < 0.001) after 16 and 52 weeks' follow-up. Risk calculations are surrogate endpoints and may not translate into actual reductions in cardiovascular events. Overall, 49.1% (low-dose PI) and 44.0% (UC) reported AEs. Conclusion: A proactive, multifactorial approach to cardiovascular management based on low-dose SPAA led to statistically significant improvements in calculated 10 year CHD risk versus physician's UC, comparable to that reported in the full CRUCIAL trial. These data will inform healthcare providers in countries where SPAA (5/10 or 10/10 mg) only are licensed.